Growth Kinetic Modelling of Efficient Anabaena sp. Bioflocculation - Rahmawati, Amalia; Rohmawati, Irma; Nurafifah, Istini; Sadewo, Brilian Ryan; Suyono, Eko Agus (Journal of Tropical Biodiversity and Biotechnology, 2024)
Bioflocculation is a harvesting technique that employs flocculant agents such as bacteria and microalgae. The benefit is the absence of a chemical-added flocculant. Because bacteria need a particular medium, microalgae flocculant agents are more effective. This study used Anabaena sp. to collect fat, protein, and carbohydrates from the Glagah consortium. Three replications of those microalgae were grown in 300 ml of Bold Basal Medium culture for eight days. On the day of harvest, flocculant microalgae (Anabaena sp.) and non-flocculant microalgae (Glagah) were combined to accomplish flocculation. On the day of harvest, parameters were observed by combining Anabaena sp. with the Glagah consortium in the ratios 1: 1, 0.5: 1, and 0.25: 1. There were three times of each parameter test. Utilizing a wavelength of 750 nm, the proportion of precipitation was calculated spectrophotometrically. Bligh and Dyer were used to measure the lipids. The phenol sulfate technique was used to calculate the amount of carbohydrates. By employing the Bradford method, proteins were quantified. Biofocculation percentages and carbohydrate content were optimum on a ratio of 0.25:1. Lipid and protein content were optimum on a ratio of 1:1.